The anticoagulant effect of therapeutic levels of dabigatran in atrial fibrillation evaluated by thrombelastography (TEG®), Hemoclot Thrombin Inhibitor (HTI) assay and Ecarin Clotting Time (ECT)*. (17th February 2018) - Solbeck, Sacha; Jensen, Annette Schophuus; Maschmann, Christian; Stensballe, Jakob; Ostrowski, Sisse Rye; Johansson, Pär I.
Abstract: Monitoring the effect of dabigatran (Pradaxa ® ) is challenging. The aim of this study was to evaluate if thrombelastography reaction time (TEG ® R) could detect the anticoagulant effect of dabigatran showing a correlation between TEG ® R, Hemoclot Thrombin Inhibitor (HTI) assay and Ecarin Clotting Time (ECT) in patients with non-valvular atrial fibrillation (NVAF). Blood samples from 35 AF patients receiving either 110 mg ( n 19) or 150 mg ( n 16) dabigatran twice daily were analyzed with TEG ®, HTI and ECT 2–3 h after dabigatran intake. All patients had prolonged TEG ® R. The patients receiving dabigatran 110 mg ×2 had a TEG ® R mean 14.2 min (range 9.1–25), a mean dabigatran concentration measured by HTI of 268.5 ng/mL (range 54–837 ng/mL) and by ECT of 355.7 ng/mL (range 40–1020 ng/mL). The corresponding numbers for patients receiving dabigatran 150 mg ×2 were TEG ® R mean of 12.5 min (range 9.2–23.2 min), mean dabigatran concentration of 179.2 ng/mL by HTI (range 26–687 ng/mL) and by ECT 225.1 ng/mL (range 42–1020 ng/mL). The two dosage groups had comparable anticoagulation demonstrated by equally prolonged TEG ® R ( p  = .909), HTI ( p  = .707) and ECT ( p  = .567). No difference in creatinine levels in the two dosage groups was observed ( p  = .204) though patients with dabigatran concentration >400 ng/mL had significantly higher creatinine levels ( p  = .001). Large individual variation of the anticoagulant response was observed. Some patients had TEG ® R values up to three times upper normal limit with immediate risk of bleeding. Our data indicate that TEG ® R reflected dabigatran levels in NVAF patients and that TEG ® R correlated to HTI and ECT.